Lithosphere - asthenosphere interactions and vertical movements : the Hoggar mountains case - (:unkn) unknown (My University, 2012)
The North-African intraplate topography is underlined by massive topographic swells associated with Cenozoic volcanism. The Tuareg Shield, which is one of these swells, consists of Precambrian basement which has been structured by the Pan-African orogeny and reaches currently an altitude of 2400 m. The Paleozoic sedimentary series are outcropping as important cuestas surrounding the topographic swell. Locally, some Mesozoic sedimentary remnants, lying unconformably over the basement, testify of its exposure during the Mesozoic. The Cenozoic volcanism, which is also taking place on the basement, shows ages from 35 Ma to Quaternary. In order to improve the knowledge of the Phanerozoic evolution of the Tuareg Shield, we performed two separated studies: geophysical modelling works, and a low temperature thermochronology study. The geophysical study consisted of the modelling of four long-distance profiles allowing imaging the lithospheric structure. We have shown that the Tuareg Shield swell is currently sustained by a strong lithospheric thinning. Moreover, we have estimated that without this thinning, the topography would be negative and that such basin, prior to thinning, would have allowed the deposition of a plurikilometric sedimentary cover. The low temperature thermochronological study has focused on two methods: apatite fission-track analysis, and apatite (U-Th)/He analysis. The latter shown that the Tuareg Shield, before an important Late Eocene exhumation, was buried under a sedimentary cover and heated at ~80°C. The fission-track analyses have shown that this heating stage of the Tuareg Shield, related to burying, occurred from 100 and 50 Ma. Thus, the Tuareg Shield was probably a wide scale sedimentary basin during the Upper Cretaceous – Paleocene. These results allowed us to discuss the geodynamic mechanisms potentially active during the Cenozoic. We proposed that the current doming of the Tuareg Shield, as well as its volcanism, were relat
Keywords: African Research